Exploration of Challenges in Team Management Faced by Managers in an IT Company - Kaczmarek, Tomasz (Analiza wyzwań w zarządzaniu zespołem stojących przed menedżerami w firmach IT, 2025)
The purpose of this research was the exploration of the challenges in team management faced by managers in an IT company. The company being the subject of this study provides solutions in Software as a Service model. It uses an agile approach, and like many other IT organizations, it faces challenges related to scaling it to the level of many teams. The company uses the idea of reverse Conway manoeuvre, the strategy in which organizations focus on organizing team structures to match the architecture they want the system to exhibit. This research tries to answer the question of how to use the topology of development teams and their environment to optimise delivery of value to customers and prevent creation of team silos. To accomplish exploration of the problem analysed, a series of individual in-depth interviews was conducted. The research presents an analysis of issues being addressed in the interviews, as well as recommendations on selected subjects.
Quote as: Kaczmarek, T. (2025). Exploration of Challenges in Team Management Faced by Managers in an IT Company. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 110-121). Publishing House of Wroclaw University of Economics and Business.
Keywords: teams management; scaled agile; silo mentality; virtual teams; Conway's law; zarządzanie zespołami; skalowanie podejścia zwinnego; mentalność silosowa; zespoły wirtualne; prawo Conwaya